Deriving Formula for Centripetal Force

The conditions for a centripetal force to be present is circular motion, specifically when the angular frequency and speed are constant. First, start off with the vector or parametric equation for circular motion about the origin. The radius of the circular path is r meters, the angular frequency of the particle is omega.

s=(xy)=(rcos(ωt)rsin(ωt)) \mathbf{s}=\begin{pmatrix}x\\ y\end{pmatrix}=\begin{pmatrix}r \cos\left ( \omega t \right )\\ r \sin\left ( \omega t \right ) \end{pmatrix}

The definition of velocity is the rate of change in displacement, so to get velocity, differentiate the position vector for the particle with respect to time.

v=ddts=(rωsin(ωt)rωcos(ωt))\mathbf{v}=\frac{d}{dt}\mathbf{s}=\begin{pmatrix}-r \omega \sin\left ( \omega t \right )\\ r \omega \cos\left ( \omega t\right )\end{pmatrix}

Velocity is not constant but if we take the magnitude, we find that its magnitude (speed) is, so the conditions for centripetal force to be present are satisfied.

v=(rω)2cos2(ωt)+(rω)2sin2(ωt)|\mathbf{v}|=\sqrt{(r\omega)^2 \cos^2 \left ( \omega t \right ) +(r\omega)^2 \sin^2 \left ( \omega t \right )}

v=rωcos2(ωt)+sin2(ωt)|\mathbf{v}|=r\omega\sqrt{\cos^2 \left ( \omega t \right ) +\sin^2 \left ( \omega t \right )}

v=rω=r2πf\therefore |\mathbf{v}|=r\omega =r 2\pi f

Acceleration is the rate of change in velocity so differentiate the velocity vector to get the acceleration vector.

a=ddtv=(rω2cos(ωt)rω2sin(ωt))\mathbf{a}=\frac{d}{dt}\mathbf{v}=\begin{pmatrix}-r \omega^2 \cos\left ( \omega t \right )\\ -r \omega^2 \sin\left ( \omega t\right )\end{pmatrix}

With this expression for acceleration, we can show that acceleration is always perpendicular to velocity, another requirement for circular motion. Velocity is perpendicular to acceleration if and only if their scalar product is zero.

vava=0\mathbf{v}\perp\mathbf{a} \Leftrightarrow \mathbf{v}\cdot\mathbf{a}=0

va=(rωsin(ωt)rωcos(ωt))(rω2cos(ωt)rω2sin(ωt))=r2ω3cos(ωt)sin(ωt)r2ω3cos(ωt)sin(ωt)=0\mathbf{v}\cdot\mathbf{a}=\begin{pmatrix}-r \omega \sin\left ( \omega t \right )\\ r \omega \cos\left ( \omega t\right )\end{pmatrix}\cdot\begin{pmatrix}-r \omega^2 \cos\left ( \omega t \right )\\ -r \omega^2 \sin\left ( \omega t\right )\end{pmatrix}=r^2\omega^3\cos \left ( \omega t \right ) \sin\left ( \omega t \right )-r^2\omega^3\cos \left ( \omega t \right ) \sin\left ( \omega t \right )=0

va\therefore \mathbf{v}\perp\mathbf{a}

Moving on, the magnitude of acceleration is

a=r2ω4sin2(ωt)+r2ω4cos2(ωt)=rω2|\mathbf{a}|=\sqrt{r^2 \omega^4 \sin^2 \left ( \omega t \right ) +r^2 \omega^4 \cos^2 \left ( \omega t \right )}=r \omega^2

Multiply by r r

ra=r2ω2=(rω)2r|\mathbf{a}| =r^2 \omega^2=\left (r \omega \right ) ^2

Substitute v=rω |\mathbf{v}|=r\omega

ra=v2r|\mathbf{a}| =|\mathbf{v}|^2

Divide by r r and we have the formula for centripetal acceleration.

a=v2r\therefore |\mathbf{a}| =\frac{|\mathbf{v}|^2}{r}

Assuming the particle has a constant mass, multiply both sides by mm and substitute the left hand side for the magnitude of the force vector because of Newton's second law. Thus we have the formula for centripetal force.

F=mv2r\therefore |\mathbf{F}| =m\frac{|\mathbf{v}|^2}{r}

Note by Jack Han
3 years, 11 months ago

No vote yet
1 vote

</code>...<code></code> ... <code>.">   Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in </span>...<span></span> ... <span> or </span>...<span></span> ... <span> to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

There are no comments in this discussion.

×

Problem Loading...

Note Loading...

Set Loading...